2014
DOI: 10.7883/yoken.67.62
|View full text |Cite
|
Sign up to set email alerts
|

MePIC, Metagenomic Pathogen Identification for Clinical Specimens

Abstract: SUMMARY: Next-generation DNA sequencing technologies have led to a new method of identifying the causative agents of infectious diseases. The analysis comprises three steps. First, DNA/RNA is extracted and extensively sequenced from a specimen that includes the pathogen, human tissue and commensal microorganisms. Second, the sequenced reads are matched with a database of known sequences, and the organisms from which the individual reads were derived are inferred. Last, the percentages of the organisms' genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…10) It is expected that bacterial identification will be performed using metagenome analysis in the future. 11) For the treatment of prosthetic vascular graft infection in the thoracic aortic area, Coselli et al 1) reported a composite of aortic graft reconstruction and omental filling procedures after re-thoracotomy and debridement in 1999, resulting in a high 1-year mortality rate of approximately 30%. In 1984, Hargrove et al 12) reported successful infection control by omental filling without removal of infected prosthetic grafts.…”
Section: Discussionmentioning
confidence: 99%
“…10) It is expected that bacterial identification will be performed using metagenome analysis in the future. 11) For the treatment of prosthetic vascular graft infection in the thoracic aortic area, Coselli et al 1) reported a composite of aortic graft reconstruction and omental filling procedures after re-thoracotomy and debridement in 1999, resulting in a high 1-year mortality rate of approximately 30%. In 1984, Hargrove et al 12) reported successful infection control by omental filling without removal of infected prosthetic grafts.…”
Section: Discussionmentioning
confidence: 99%
“…However, some outbreaks of RV infection in adults have been reported (5). This report describes an outbreak of gastroenteritis due to genotype G1P [8] RV in adolescents in Tochigi prefecture, Japan.…”
mentioning
confidence: 92%
“…The obtained raw short reads ($1 million reads per sample) were analyzed by the MePIC server (8) to characterize potential pathogens. Sequence analysis of VP4 and VP7 genes by NGS suggested that this sample contained G1P [8] rotavirus. Therefore, VP4 and VP7 genes of RV were amplified and detected from all of the samples using nested RT-PCR (9, 10).…”
mentioning
confidence: 93%
See 2 more Smart Citations